Implementation Of General Principles Of Good Government In The Organization Of The 2024 Elections - M. Reza Saputra; Wicipto Setiadi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research uses empirical legal methods to examine the integrity and credibility of the 2024 election organizers in Indonesia. Data was collected from various sources, including MK decisions, DKPP, election observer reports, academic publications, and related news. Data analysis was carried out to identify patterns, trends and implications for the integrity and credibility of election organizers, as well as evaluate the implementation of the General Principles of Good Government (AUPB) in organizing elections. The main objective of this research is to update the electoral system in Indonesia and ensure that elections are of quality, integrity and reliability. The research approach focuses on collecting empirical data from concrete cases during the 2024 Election and in-depth analysis of this data to identify emerging patterns and trends. Data analysis aims to evaluate the influence of political intervention, conflicts of interest, and compliance with legal rules and decisions on the integrity and credibility of election organizers. The results of the research will be compiled in a report that includes in-depth analysis of concrete cases, policy recommendations to improve the integrity and credibility of election organizers, as well as suggestions for improving the implementation of AUPB in the 2024 Election. This research is expected to provide a better understanding of the challenges and opportunities to ensure the integrity and credibility of election organizers in Indonesia, as well as providing concrete steps to improve the implementation of AUPB principles in the election context.